2017
DOI: 10.1167/iovs.16-20804
|View full text |Cite
|
Sign up to set email alerts
|

Glial Cell Contribution to Basal Vessel Diameter and Pressure-Initiated Vascular Responses in Rat Retina

Abstract: PurposeThe purpose of this study was to test the hypothesis that retinal glial cells modify basal vessel diameter and pressure-initiated vascular regulation in rat retina.MethodsIn rats, L-2-aminoadipic acid (LAA, 10 nM) was intravitreally injected to inhibit glial cell activity. Twenty-four hours following injection, retinal glial intracellular calcium (Ca2+) was labeled with the fluorescent calcium indicator Fluo-4/AM (F4, 1 mM). At 110 minutes after injection, intraocular pressure (IOP) was elevated from 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
12
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 25 publications
1
12
1
Order By: Relevance
“…We previously showed that the pharmacologic inhibition of glial activity increased the basal venular diameter and compromised the responses of both the arterioles and the venules to a rapid increase in the IOP. 11 These data are consistent with the possibility that glial cells participate in the maintenance of both basal venular tone and the regulation of vascular resistance in response to changes in the local pressure environment. However, the rapid IOP elevation used in our previous study can introduce an abrupt compression of the vessels, which may complicate interpretation.…”
supporting
confidence: 83%
See 2 more Smart Citations
“…We previously showed that the pharmacologic inhibition of glial activity increased the basal venular diameter and compromised the responses of both the arterioles and the venules to a rapid increase in the IOP. 11 These data are consistent with the possibility that glial cells participate in the maintenance of both basal venular tone and the regulation of vascular resistance in response to changes in the local pressure environment. However, the rapid IOP elevation used in our previous study can introduce an abrupt compression of the vessels, which may complicate interpretation.…”
supporting
confidence: 83%
“… 10 We previously demonstrated that perivascular glia in rat retina were activated in response to acute IOP elevation, as evidenced by increased intracellular calcium concentration. 11 Pharmacologic inhibition of glial activity significantly blunted calcium activation and impaired the capacity for the vasculature to respond to IOP elevation. This finding is consistent with the results of Kim et al, 9 which showed that the inhibition of astrocyte activation (decreased calcium activity) attenuated compensatory vascular responses to an acute, phenylephrine-induced elevation of the systemic blood pressure (BP).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, endothelial dysfunction may contribute to an imbalance of diameter regulation in diabetes (Pemp et al 2009). Recent evidence also suggests that retinal glial cells are capable of sensing the reduction in perfusion pressure and contribute to the maintenance of vessel diameters (Li et al 2017). Since glial cells are affected early in the diabetic retina and continue to degenerate along with retinal ganglion cells (Coughlin et al 2017), neuroretinal damage may be another important factor in disturbed retinal vascular autoregulation.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, in response to a relatively low magnitude IOP elevation (10-40 mm Hg), vasodilation occurs to prevent a drop in blood flow. 8,9 When IOP elevation reaches 60 to 70 mm Hg, autoregulation mechanisms are overwhelmed resulting in forceful compression of inner retinal vessels and attenuation of blood flow. 10 Although many studies have documented autoregulation-induced changes in the larger surface vessels, few have considered the smaller vessels.…”
mentioning
confidence: 99%